The Gospel According to Matthew - Reid, Barbara E. (Collegeville, Minn. : Liturgical Press, 2005)
"Complete biblical texts with sound, scholarly based commentary that is written at a pastoral level; the Scripture translation is that of the New American Bible with Revised New Testament and Revised Psalms (1991)"--Provided by publisher.
The origins of Jesus (1:1-4:11) -- The beginnings of the Galilean ministry (4:12-10:42) -- The Sermon on the Mount (5:1-7:28) -- Varying responses to Jesus (11:1- 16:12) -- Jesus and his disciples on the way to Jerusalem (16:14-20:34) -- Jerusalem : Jesus' final days of teaching in the temple (21:1-28:15) -- Finale: Back to Galilee; Commission to the whole world; Jesus' abiding presence (28:16-20).
Keywords: Bible. -- Commentaries; Matthew